Limits determination of microbial contamination present on surfaces from a pharmaceutical microbiology district reference laboratory - Natalia Charry; Sandra L. Gómez (Journal of Pharmacy & Pharmacognosy Research, 2016)
Context: The bioburden present on the pharmaceutical microbiology laboratory’s surfaces, may increase the risk of cross-contamination when analytical tests are being carried out; periodic monitoring allows to set limits that reduce the risk.